Discrimination and International Trade Policy - Mikesell, Raymond F. (The Review of Economics and Statistics, 1950)
NON-discrimination and multilateral payments represent the foundations of United States foreign trade and exchange policy. The United States has sought to implement this policy through multilateral agreements, such as the International Monetary Fund Agreement and the Charter for an International Trade Organization, and through bilateral agreements, such as the Anglo-American Financial Agreement.' Most American economists and statesmen consider the universal desirability of nondiscrimination to be a self-evident truth readily deducible from the first principles of economics. But in recent years a number of reputable economists have come forth with strong arguments in favor of trade and exchange discrimination, and these arguments have had an important influence on the formation of international economic policy. It is not enough for economists of the free-trade school to refute these arguments by an application of the principles of classical economics, since the proponents of trade discrimination usually begin by denying the classical postulates.2 Rather the problem must be examined within the institutional framework of the postwar world and its solution worked out in a manner consistent with current economic and political realities. Although the economist would be derelict if he assumed the world as it currently exists as inevitable and incapable of change in response to his counsel, mere deduction from first principles is not likely to solve its problems. The purpose of this paper therefore is to analyze the case for discrimination as objectively and sympathetically as possible, with a view to determining the extent to which the problems that the proponents of discrimination have posed can be dealt with a minimum of violence to the wellknown advantages of non-discriminatory and multilateral trade.